Risk Factor Analysis of Diarrhea in Medical Students - Warda Elmaida Rusdi; Irmawan Farindra; Muhammad Salsabeela Rusdi; Irsandi Rizky Farmananda; Ayu Aisyah Alya Hamida (Jambi Medical Journal : Jurnal Kedokteran dan Kesehatan, 2023)
ABSTRACT Background: Diarrhea is a condition of increased frequency of defecation more than 3 times along with liquid stool consistency followed by mucus or blood. In Indonesia alone in 2019, the reported incidence of diarrhea was 2,549 people with a case fatality rate of 1.14%. This study aims to analyze the risk factors for diarrhea in university students. Methods: This study is an observational analytic descriptive study with a cross sectional study design. This study used a sample of 132 students who were determined by purposive sampling technique. Questionnaires were used as data collection instruments. Data analysis was carried out using bivariate and univariate tests with logistic regression techniques with a p <0.05 indicating data significant. Results: Based on the research that has been done, 54 male subjects and 78 female subjects were obtained. Most of the research subjects experienced diarrhea with a frequency of 3 to 4 times a month (55.3%) which was associated with environmental and psychological factors with significant levels of p < 0.043 and p < 0.049, respectively. Conclusion: Environmental and psychological factors have a significant relationship partially with the incidence of diarrhea in students of the Faculty of Medicine, Universitas Nahdlatul Ulama Surabaya.